各阶段口译员在医疗口译中的 "错误" 实证研究—以中医医疗口译为例 = An empirical study of interpreters' 'errors' in healthcare settings: the case of traditional Chinese medicine interpreting - Geng, Bowen (Nanyang Technological University, 2023)
本研究是一项聚焦于医疗口译错误的实证研究。旨在与探讨三组受试者在医疗口译中出现的错误类型和原因、三组间错误数量的差别、错误数量与受试者口译受训时长和口译实践场次的相关性，并提出提高医疗口译质量的建议。 本研究招收了三组，共56位受试者，包括20位初级口译学生、20位高级口译学生和和16位职业口译员。每位口译了四段发生在中医情景下的中-英问诊对话，接受了口译回顾性采访和开放式采访，并填写了一份问卷。数据分析采用了质化和量化分析两种方法，对错误的类型和原因、三组间错误数量差异、错误数量与受试者口译受训时长和口译实践场次的关系进行了探究。 研究结果显示受试者共产出了24种口译错误，可分为3大类：信息传递错误、非流利现象和语言错误。受试者口译能力的欠缺、处理能力饱和、注意力资源分配的不合理、某些口译策略的使用及源语的负迁移是造成错误的主要原因。三组受试者并不在所有的错误类型上都存在显著差别。大多数错误和受试者口译受训时长和口译实践场次的负相关。基于此，为提高医疗口译质量提出了建议。 本研究丰富了医疗口译错误体系，拓宽了医疗口译错误的影响因素和犯错原因的研究视野，说明了现有教学的局限性和开展专门针对医疗口译教学的必要性。对医疗口译研究、实践和教学具有一定的启示。 This empirical study focuses on errors of interpreters in healthcare interpretation. This study aims to explore the types and causes of the errors in healthcare interpretation, the statistical difference in types of errors among three groups of participants, the correlation between errors and participants’ training and practice, and to propose guidelines towards improving the quality of healthcare interpretation. Three groups, totaling 56 interpreter-participants, were recruited for this study: 20 beginning students, 20 advanced students, and 16 professional interpreters. Each participant was asked to consecutively interpret four recorded conversation segments between a Traditional Chinese Medicine practitioner and an English-speaking patient, followed by a simulated retrospective interview, an open interview and a questionnaire. A combination of qualitative and quantitative analysis was later adopted for data analysis to accomplish the above-mentioned study objectives. The analysis revealed 24 types of errors that can be classified into three categories: information errors, disfluencies and linguistic errors. These errors were mainly caused by participants’ lack of competence in performing interpretations, cognitive overload, inappropriate allocation of available attentional resources, adoption of certain strategies, or interference from the source language (i.e., Chinese). There were error categories where the differences between the three groups were statistically insignificant, and most error types were negatively correlated with their training and practice. Based on the above findings, suggestions were provided on how to better train healthcare interpreters. This dissertation therefore expands the typology of healthcare interpretation errors and broadens the potential scope of future research on factors that contribute to errors and reasons that lead to errors in healthcare interpretation. The findings of this study also shed light on the limitations in existing training programs and the need for specialized training in healthcare interpreting, thereby contributing to the research, practice and teaching of healthcare interpreting.